Tinjauan Yuridis Tentang Distribusi Garam di Daerah Jono(Studi Kasus di Desa Jono Kecamatan Tawangharjo Kabupaten Grobogan) - Sulastiono, Heru, Dr. Kelik Wardiono, S.H., M.H (2017)
The purpose of this study was to determine the distribution pattern of the salt and analyzing legal protection for businesses involved in the distribution of salt in the Village Jono Tawangharjo Subdistrict Grobogan. This research includes empirical juridical legal research / sociological. The research was conducted in the village Jono Tawangharjo Subdistrict Grobogan. The data source using primary data. Data were analyzed using qualitative analysis. The results showed that: First, the distribution pattern of the salt in the Village Jono Tawangharjo Subdistrict Grobogan is using indirect distribution pattern that is producing salt involve others to help distribute salt to consumers (brokers, dealers / agents, as well as small and medium enterprises); Second, the legal protection for businesses involved in the distribution of salt in the Village Jono Tawangharjo Subdistrict Grobogan: (a) Liability traders buy salt from farmers; (b) The obligation of the salt industry to process through the washing process and iodized; (c) the import of salt is tightened to provide protection and improve the profitability of the salt. Keywords: Salt distribution patterns, Legal Protection for Distribution Garam Executors